EFEKTIVITAS PERMAINAN PUZZLE TEBAK GAMBAR TERHADAP KEMAMPUAN MENGHAFAL MUFRODAT PESERTA DIDIK PADA MATA PELAJARAN BAHASA ARAB - Bulqis Bulqis; Nelly Mujahidah; Media Aprilyanti (Armala, 2022)
The purpose in this study are: To acknowledge the ability of student to memorize the vocabularies before dan after using the puzzle of guessing picture’s game in Arabic subjects Class III Private Islamic Elementary School NU 2 Pontianak Academic Year 2021/2022. To acknowledge the effectiveness of the puzzle guessing picture’s game on the ability to memorize vocabularies for students' in the Arabic language subject Class III Private Islamic Elementary School NU 2 Pontianak Academic Year 2021/2022. The type of research in this study is descriptive quantitative with the research design used, namely the One Group Pretest Posttest Design. The population of this study was all students of class III Private Islamic Elementary School NU 2 Pontianak with a total of 19 people. Meanwhile, the sample that the researchers used, namely saturated sampling. The data analysis techniques used are descriptive statistical analysis and N-Gain Score test. The results showed that: The ability to memorize student vocabularies before using the puzzle of guessing picture’s game in arabic language obtained an average of 75.26 which is included in the moderate category, and after using the picture guessing puzzle game in the arabic language obtained an average of 90.79 which is included in the very high category. The effectiveness of the picture guessing puzzle game on the ability to memorize the vocabularies of students in the Arabic subject is categorized as quite effective.